Social Studies Teachers’ Awareness and Attitude to Environmental Education among Secondary School teachers in Ibadan, Oyo State, Nigeria - Itasanmi, Babalola Stephen (NIU Journal of Social Sciences, 2020)
The study assessed Social Studies teachers’ awareness of and attitude to Environmental Education among Secondary School teachers in Ibadan. Twenty-six secondary schools were randomly selected across the eleven local governments in Ibadan using sixty-nine Social studies teachers. It assessed social studies teachers’ attitude to objectives and methods used in teaching Environmental Education as well as their view on the role they are to play in Environmental Education. The study made use of primary source of data, using a likert type questionnaire which tested areas of attitude and methodology with the descriptive and inferential statistics. Findings are based on 5% level of significance. The study identified no significant effect of gender, training in environmental awareness and experience in teaching social studies. It also revealed that teachers have positive attitude towards environmental education. Keywords: Environmental Education, Environmental Awareness, Attitude